CYBERBULLYING AMONG FEMALE COLLEGE STUDENTS IN SAUDI ARABIA - Nawal A. Alissa; Rawan Abu Shryei (International Journal of Child, Youth & Family Studies)
In this cross-sectional study, we investigated cyberbullying among 203 female college students in Saudi Arabia during January and February 2020. The participants were randomly selected from each of the 12 colleges in the female campus of King Saud University in Riyadh City. The participants completed self-administered surveys adapted from the Compendium of Assessment Tools for Measuring Bullying Victimization, Perpetration, and Bystander Experiences, published by the Centers for Disease Control and Prevention. The findings of this study revealed that 41.6% of the sample had encountered some form of cyberbullying at least once in their lifetime. On the other hand, 15.8% reported cyberbullying others. The primary motivations for cyberbullying others were fun and vengeance. The majority of victims (16.3%) did not tell anyone that they were being cyberbullied. Only 2.0% to 2.5% reported an overlap between offline and online bullying. The study’s findings indicate that female college students would benefit from comprehensive cyberbullying education and awareness campaigns. Additionally, interventions to combat cyberbullying within the population are needed.